Resilience in Pandemic Sensemaking: Thinking Through a Community of Practice - Luka, Mary Elizabeth (Imaginations)

(untitled) (York University, 2021)
In the fall of 2020, a series of videos created for the exploratory shared experience called Massive Micro Sensemaking were presented at the Virtual International Arts (VIA) Festival for Social Change in New York. In this article, Luka considers these works as caring, reflective and expressive practices of resilience during a global crisis, while questioning who benefits from promoting ideas about social resilience in such circumstances.